The Strategies Role of Tax Management Effectiveness in Corporate Tax Compliance: Financial Condition, Tax Understanding, and Tax Awareness - Kriswardhani, Anova Pepsy; Lestari, Wiwik (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: This research fosters a conceptual framework for tax compliance behavior by integrating economic and social psychological perspectives through the Slippery Slope Framework. This concept postulates that taxpayer compliance is affected by two primary dimensions, specifically the power of tax authorities and taxpayers’ trust in authorities. Methodology/approach: In this research, a survey-based quantitative approach was utilized to examine the effects of financial condition, tax understanding, and taxpayer awareness on corporate taxpayer compliance, in addition to observe the moderating role of tax management effectiveness. The research was administered during the period 22 December 2025 to 11 January 2026. Data were collected from corporate taxpayers registered at KPP Pratama Surabaya Sukomanunggal. The data were analyzed using SmartPLS version 4.1.1.6. A total of 100 corporate taxpayers were selected using purposive sampling. Findings: The findings discovered that financial conditions did not have any noteworthy effect upon corporate taxpayer compliance. Besides, tax understanding and taxpayer awareness results had positive and significant influence on corporate taxpayer compliance. Furthermore, tax management effectiveness did not moderate the relationships among financial conditions, tax understanding, and taxpayer awareness toward corporate taxpayer compliance. Practical implications: This study suggests that tax authorities should prioritize improving taxpayers’ understanding and awareness to enhance compliance, rather than focusing primarily on financial conditions or tax management effectiveness. Originality/value: This research delivers theoretical contributions to the tax compliance literature and recommends concrete suggestions for tax authorities in recommending policies and approaches to expand corporate taxpayer compliance.